High‐temperature tensile behavior at different crosshead speeds during loading of glass fiber‐reinforced polymer composites. Issue 16 (12th January 2017) - Mahato, Kishore Kumar; Dutta, Krishna; Ray, Bankim Chandra
ABSTRACT: The present study evaluates on the static tensile behavior of glass fiber reinforced polymer (GFRP) composites at 50% and 70% volume fractions of reinforcement tested at room (25 °C), 70 °C, 90 °C, and 110 °C temperatures with 1, 10, 100, 500, and 1000 mm/min crosshead speeds to investigate the impact of high temperature on the mechanical properties and different dominating failures modes. The experimental results reveal that with increase in crosshead speeds the tensile strength of the composite is increasing. The effect of crosshead speeds and temperature with changing fiber volume fractions affects the GFRP composite. Although both the composite systems are found to be crosshead speed sensitive. Crosshead speed sensitivity seems to be more unpredictable at high temperature and at high crosshead speed. Furthermore, it appears to be more unprecedented nature of fluctuation with high fiber volume fraction. The crucial parameters required during the materials designing in various structural components were evaluated and modelled with the help of Weibull constitutive model. The fractography analyses were done to identify the various dominating failure modes in the GFRP composite. There was no significant change found in the glass transition temperatures ( Tg ) of both the composite system when exposed to different temperature environments. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44715. Abstract :